2017
DOI: 10.1371/journal.pone.0185391
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of shear wave elastography (SWE) in patients with chronic liver disease

Abstract: The presence of significant fibrosis is an indicator for liver disease staging and prognosis.The aim of the study was to determine reproducibility of real-time shear wave elastography using a hepatic biopsy as the reference standard to identify patients with chronic liver disease. Forty patients with chronic liver disease and 12 normal subjects received shear wave elastography performed by skilled operators. Interoperator reproducibility was studied in 29 patients. Fibrosis was evaluated using the Metavir scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 35 publications
(33 reference statements)
4
28
0
Order By: Relevance
“…In our study, a median of six SWV measurements was the minimum number required that resulted in an error rate of less than 5% compared with a median of 10 measurements. In addition, the 95% agreement limit from the Bland Altman analysis was also comparable to the 95% agreement limit from interobserver variability previously described (26). The area under the receiver operating characteristic curve GASTROINTESTINAL IMAGING: Reducing the Number of Measurements in Liver Point Shear-Wave Elastography Fang et al rate with histologic evaluation for differentiating between significant and severe fibrosis or cirrhosis, respectively, compared with patients with higher reliability measurements (IQR-to-median ratio, 30%).…”
Section: Discussionsupporting
confidence: 74%
“…In our study, a median of six SWV measurements was the minimum number required that resulted in an error rate of less than 5% compared with a median of 10 measurements. In addition, the 95% agreement limit from the Bland Altman analysis was also comparable to the 95% agreement limit from interobserver variability previously described (26). The area under the receiver operating characteristic curve GASTROINTESTINAL IMAGING: Reducing the Number of Measurements in Liver Point Shear-Wave Elastography Fang et al rate with histologic evaluation for differentiating between significant and severe fibrosis or cirrhosis, respectively, compared with patients with higher reliability measurements (IQR-to-median ratio, 30%).…”
Section: Discussionsupporting
confidence: 74%
“…RTE can differentiate malignant from benign thyroid nodules because malignant nodules are harder than the surrounding adjacent parenchyma (23)(24)(25)(26)(27). Several meta-analyses suggest that RTE is superior to SWE for this purpose (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In healthy participants, the intraobserver repeatability of 2D SWE was excellent (ICC ranged from 0.92-0.95), 22,27,28 and the interobserver agreement across different days was good (ICC ranged from 0.63-0.88). 22,28 In patients with chronic liver disease, Yoon et al 15 reported excellent overall intraobserver repeatability (ICC, 0.95), and Mancini et al 29 reported excellent interobserver agreement (ICC, 0.94). These previously published studies showed that experience, patient age, and disease, as well as different days, liver segments, and times of examinations, can affect the repeatability of the measurements.…”
Section: Discussionmentioning
confidence: 99%